How Slow RNA Polymerase II Elongation Favors Alternative Exon Skipping - Dujardin, Gwendal (2014)
Splicing is functionally coupled to transcription, linking the rate of RNA polymerase II (Pol II) elongation and the ability of splicing factors to recognize splice sites (ss) of various strengths. In most cases, slow Pol II elongation allows weak splice sites to be recognized, leading to higher inclusion of alternative exons. Using CFTR alternative exon 9 (E9) as a model, we show here that slowing down elongation can also cause exon skipping by promoting the recruitment of the negative factor ETR-3 onto the UG-repeat at E9 3′ splice site, which displaces the constitutive splicing factor U2AF65 from the overlapping polypyrimidine tract. Weakening of E9 5′ ss increases ETR-3 binding at the 3′ ss and subsequent E9 skipping, whereas strengthening of the 5′ ss usage has the opposite effect. This indicates that a delay in the cotranscriptional emergence of the 5′ ss promotes ETR-3 recruitment and subsequent inhibition of E9 inclusion.